The interaction between IT and planning: decision support or knowledge generation? (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2022)
The present study aims to discuss, under a theoretical perspective, the role and the added value of the interaction between Information Technology (IT) and decision-making, paying particular attention to the planning context. The main idea of this paper is that the interaction of decision makers with IT, especially when the decisions concern scenario planning and alternative hypotheses, plays two important roles: a) it supports decisions, given the availability of semi-structured information and data provided by IT tools; b) it generates knowledge due both to the iterative approach followed by the decision maker for designing the planning model and to the reasonings and group discussions about the objectives to be defined. The conclusions speculate that the interaction between IT and decision makers is not limited to provide decisional support, but it also generates knowledge and promotes a learning process, especially in a complex decision domain. Therefore, further research is encouraged on this issue, for examining to what extent, and under which conditions, the interaction with IT allows to generate or increase knowledge about a problem, beyond a mere decision support.